Adopsi Inovasi Pupuk Organik untuk Pengelolaan Lingkungan Berkelanjutan di Kecamatan Tilongkabila Provinsi Gorontalo - Angela Apriliany Abdullah; Supriyo Imran; Zulham Sirajuddin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
After the green revolution, the awareness of the importance of using organic fertilizers has increased. However, farmers' interest in adopting organic fertilizers is still shallow. The aims of this study were (1) to determine the extent to which farmers adopted organic farming and (2) to determine what variables influenced farmers' decisions to adopt organic fertilizers. This study was conducted in 2022 in Tilongkabila District, Bone Bolango Regency, Gorontalo Province, one of the leading agricultural areas in Bone Bolango Regency, with a total respondent of 213 farmers. The results of this study indicated that farmers' adoption rate in organic fertilizers based on the innovation-decision stages of adopters was still relatively low, where as many as 35% of farmers have adopted organic fertilizer innovations. Meanwhile, the compatibility attribute is the only variable that could predict farmers' adoption of organic fertilizer innovations in the Tilongkabila District.